Nordic Cooperation in the Nuclear Safety Sector: High, Low, or Differentiated Integration? - Kjøndal, Kjerstin (2020)
Nordic cooperation has been depicted as eroding due to the increased importance of EU-related cooperation and integration. However, scholars propose that longstanding Nordic networks, grounded in professions and located in the state administration, may prove to be more robust toward external changes. This article discusses this proposal by looking at Nordic cooperation between the national radiation protection and nuclear safety authorities in Iceland, Denmark, Norway, Sweden, and Finland. The article maps behavioural perceptions of agency staff based on a dataset of 37 interviews to illustrate if the cooperation between the Nordic authorities is characterized by high integration, low integration, or differentiated integration within the nuclear safety sector. The study finds that the cooperation is differentiated between the highly integrated areas of radiation protection and emergency preparedness, and the less integrated areas of nuclear security and safeguards. To account for variation, the data indicates the importance of path dependency and portfolio.